2021
DOI: 10.3390/molecules27010078
|View full text |Cite
|
Sign up to set email alerts
|

Rosmanol and Carnosol Synergistically Alleviate Rheumatoid Arthritis through Inhibiting TLR4/NF-κB/MAPK Pathway

Abstract: Callicarpa longissima has been used as a Yao folk medicine to treat arthritis for years in China, although its active anti-arthritic moieties have not been clarified so far. In this study, two natural phenolic diterpenoids with anti-rheumatoid arthritis (RA) effects, rosmanol and carnosol, isolated from the medicinal plant were reported on for the first time. In type II collagen-induced arthritis DBA/1 mice, both rosmanol (40 mg/kg/d) and carnosol (40 mg/kg/d) alone alleviated the RA symptoms, such as swelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Schwager et al also showed that CS inhibits cytokine production and NFκB activation in murine macrophages and human chondrocytes [ 87 ]. In addition to its in vitro effects, CS also reduced serum or tissue levels of cytokines with inhibition of the NFκB pathway in animal models of inflammatory diseases such as spinal cord injury [ 16 ], atopic dermatitis [ 19 ] and rheumatoid arthritis [ 88 ]. In this study, we also found that CS suppressed infiltration of neutrophils and macrophages in kidneys of UUO mice, as indicated by reduced MPO activity and decreased numbers of Ly6B.2-positive cells and F4/80-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Schwager et al also showed that CS inhibits cytokine production and NFκB activation in murine macrophages and human chondrocytes [ 87 ]. In addition to its in vitro effects, CS also reduced serum or tissue levels of cytokines with inhibition of the NFκB pathway in animal models of inflammatory diseases such as spinal cord injury [ 16 ], atopic dermatitis [ 19 ] and rheumatoid arthritis [ 88 ]. In this study, we also found that CS suppressed infiltration of neutrophils and macrophages in kidneys of UUO mice, as indicated by reduced MPO activity and decreased numbers of Ly6B.2-positive cells and F4/80-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…; the current treatment of such diseases is still mainly to relieve the clinical symptoms by using anti-inflammatory analgesics and immunosuppressants [ 4 ]. With the continuous development of molecular studies, some studies have pointed out that the activation of TLRs can promote human immune defense function, among which Toll-like Receptor 4 (TLR4) plays an important role in regulating immune response and promoting the secretion of inflammatory factors, and can activate Nuclear Factor kappa-B (NF- κ B) to promote gene transcription [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…RA reduced the arthritic index by reducing the frequency of COX‐2‐expressing cells 67 . In addition, RO and CA could decrease the serum pro‐inflammatory cytokine levels of IL‐6, MCP‐1, and TNF‐α by blocking the activation of the TLR‐4/NF‐κB/JNK pathways in rheumatoid arthritis mice 93 . Another study showed that RA significantly decreased the arthritic score and levels of TNF‐α in Wistar albino rats 68 .…”
Section: Resultsmentioning
confidence: 98%